Lemak Viseral, Bukan Lemak Biasa : Faktor Dominan dalam Regulasi Oil, Water, dan Hidrasi Kulit pada Dokter Muda - Gina Triana Sutedja; Fiona Valencia Setiawan (Jurnal Kesehatan Amanah, 2025)
Visceral fat is metabolically active adipose tissue and plays a key role in the pathogenesis of various cardiometabolic diseases. The accumulation of visceral fat not only impacts systemic health but is also thought to be linked to the condition of the skin, which is the body's largest organ and sensitive to metabolic changes. This study aimed to explore the relationship between visceral fat and skin health indicators, including oil content, water content, and skin hydration in a population of young physicians. This group was selected because, although relatively clinically healthy, they are susceptible to subclinical metabolic disorders due to suboptimal work patterns and lifestyles. The study used a cross-sectional design on 96 young physicians at the Faculty of Medicine, Tarumanagara University. Data were collected through anthropometric measurements, body composition analysis using bioimpedance, skin examination with a skin analyzer, and blood lipid profiles. Spearman correlation analysis was used to assess the relationship between the study variables. The results showed that visceral fat had a significant positive correlation with oil content (r = 0.331; p = 0.001), skin water content (r = 0.338; p = 0.001), and skin hydration (r = 0.297; p = 0.004). This makes visceral fat the only body parameter that correlates consistently with all indicators of skin health. In contrast, blood LDL levels were negatively correlated with skin hydration (r = -0.222; p = 0.030), while other parameters did not show a significant relationship (p > 0.05). The conclusion of this study is that increased visceral fat is closely related to increased oil, water, and skin hydration levels through metabolic and inflammatory mechanisms, even in young, apparently healthy individuals. These findings emphasize the importance of visceral fat screening and the implementation of healthy lifestyle interventions as preventive measures to maintain skin health while reducing the risk of metabolic disorders.